2018
DOI: 10.1111/odi.12990
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional anticaries peptides with antibacterial and remineralizing effects

Abstract: Objectives Initial dental caries often occurs in clinic. Reduction of cariogenic bacteria and promotion of remineralization are effective ways to control them. This study was to develop bifunctional anticaries peptides with antibacterial and remineralizing properties. Methods We designed peptides TDH19, TNH19, and TVH19 and selected one through comparing their minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs) against Streptococcus mutans and their reaction on mineralizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
(73 reference statements)
0
30
0
Order By: Relevance
“…Nowadays, study groups developed an increasing number of novel synthetic AMPs with confirmed antibacterial potential. Wang et al [88] synthesized TVH19 and testified its effect on inhibiting the biofilm formation and destroying the biofilm structure of S. mutans. Min et al [13] synthesized CLP-4 and demonstrated that CLP-4 could kill S. mutans cells, inhibit biofilm formation, and eradicate preformed biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, study groups developed an increasing number of novel synthetic AMPs with confirmed antibacterial potential. Wang et al [88] synthesized TVH19 and testified its effect on inhibiting the biofilm formation and destroying the biofilm structure of S. mutans. Min et al [13] synthesized CLP-4 and demonstrated that CLP-4 could kill S. mutans cells, inhibit biofilm formation, and eradicate preformed biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…As the most common oral disease, caries occurs when the dynamic equilibrium of demineralization and re-mineralization of the dental hard tissue is upset due to the influence of biofilm and various other factors [13]. Fluoridated toothpaste contains fluoride (F), which can control caries by reducing demineralization of enamel, promoting the re-mineralization of enamel and inhibiting the metabolism of bacteria [47].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the radiopaque remineralizing zone of the enamel slice was thicker on samples treated with TVH19 or NaF but did not change significantly on the water‐treated control slices. Significantly greater mineral deposition and shallower lesions were observed in the TVH19‐treated group or NaF‐treated group than in the water‐treated control (Wang et al, ). These results suggest that bifunctional fusion peptides may both target S. mutans and promote remineralization of initial caries and have utility in the treatment of dental caries.…”
Section: Antimicrobial Peptide‐based Mimeticsmentioning
confidence: 99%
“…Recently, GH12 was fused with peptide TD7 (TKREEVD) derived from the hydrophilic C‐terminal region of amelogenin which functions to promote hydroxyapatite nucleation and the growth of enamel crystals (Li et al, ) in order to create a bifunctional peptide with both antibacterial and mineral promoting activity (Wang et al, ). The initial fusion protein exhibited poor antibacterial activity but substituting Gln for Glu 4,5 and Val for Asp 7 in TD7 to generate peptide TVH19 (Table ) significantly increased activity against S. mutans .…”
Section: Antimicrobial Peptide‐based Mimeticsmentioning
confidence: 99%